Enantioselective, Stereoconvergent Resolution Copolymerization of Racemic cis‐Internal Epoxides and Anhydrides. Issue 11 (4th February 2021) - He, Guang‐Hui; Ren, Bai‐Hao; Chen, Shi‐Yu; Liu, Ye; Lu, Xiao‐Bing
Abstract: Unprecedented enantioselective resolution copolymerization of racemic cis‐internal epoxides and anhydrides was mediated by dinuclear aluminum complexes with multiple chirality, affording optically active polyesters with two contiguous stereogenic centers, and the unreacted substrates in good enantioselectivity. Unexpected stereoconvergence is observed in this resolution copolymerization, where the selectivity factor for the enantioselective formation of copolymer significantly exceeds the kinetic resolution coefficient based on the unreacted epoxide at various conversions. Catalytic activity and copolymer enantioselectivity are strongly influenced by the phenolate ortho‐substituents of the ligand set, as well as the axial linker and its chirality. An enantiopure binaphthol‐linked bimetallic Al III complex allows stereoconvergent access to the stereoregular semi‐crystalline polyesters and a concomitant kinetic resolution of the epoxide substrates. Abstract : Stereoconvergence is observed in the enantioselective resolution copolymerization of racemic cis ‐internal epoxides and anhydrides mediated by dinuclear aluminum complexes with multiple chirality, where the selectivity factor for chiral copolymer formation significantly exceeds the kinetic resolution coefficient based on the unreacted substrate at various conversions.